Invariant varieties of periodic points for the discrete Euler top - Saito, S.; Saitoh, N. (Symmetry, Integrability and Geometry: Methods and Applications, 2006)
The behaviour of periodic points of discrete Euler top is studied. We derive invariant varieties of periodic points explicitly. When the top is axially symmetric they are specified by some particular values of the angular velocity along the axis of symmetry, different for each period.